Composition containing silane-treated calcium carbonate

JP2026535062APending Publication Date: 2026-10-22SPECIALTY MINERALS MICHIGAN INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2026521870
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-11-07
Filing Date
2024-10-10
Publication Date
2026-10-22

Smart Images

  • Figure 2026535062000007
    Figure 2026535062000007
  • Figure 2026535062000008
    Figure 2026535062000008
  • Figure 2026535062000009
    Figure 2026535062000009
Patent Text Reader

Abstract

The sealant, adhesive, and rubber composition may contain a polymer matrix and silane-treated calcium carbonate, thereby providing a composition with improved mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] (Cross-reference of related applications) This application claims priority to U.S. Provisional Patent Application No. 63 / 543,853, filed on 12 October 2023, and U.S. Patent Application No. 63 / 596,936, filed on 7 November 2023, the entirety of which disclosures are incorporated herein by reference, respectively.

[0002] (Field of invention) This disclosure relates to compositions containing silane-treated calcium carbonate, and more particularly to sealant, rubber, and / or adhesive compositions containing silane-treated calcium carbonate as a filler. [Background technology]

[0003] Calcium carbonate products have been used as fillers in sealants and rubbers. A typical calcium carbonate used as a filler in such products is fatty acid-coated calcium carbonate. The nonpolar tail of the fatty acid can provide the necessary interaction and dispersion of the filler within the polymer matrix. [Overview of the Initiative]

[0004] The compositions of the present disclosure comprise a polymer matrix and a filler containing silane-treated calcium carbonate. The compositions of the present disclosure may be sealants, adhesives, or rubber compositions. Compared to compositions using fatty acid-treated precipitated calcium carbonate (PCC) as a filler, the compositions of the present disclosure exhibit significantly improved mechanical properties such as tensile strength and / or modulus. [Brief explanation of the drawing]

[0005] [Figure 1] This disclosure includes photographs showing a pack water test of PCC treated with silane in accordance with this disclosure. [Figure 2] This graph shows comparative tensile strength tests between the composition according to this disclosure and a control composition containing PCC treated with stearic acid as a filler. [Figure 3] This graph shows a comparison of the tensile stress in a 300% elongation test between the composition according to this disclosure and a control composition containing PCC treated with stearic acid as a filler. [Figure 4] This graph shows a comparative viscosity test between the composition according to this disclosure and a control composition containing PCC treated with stearic acid as a filler. [Modes for carrying out the invention]

[0006] The compositions according to this disclosure comprise a polymer matrix and a filler containing silane-treated calcium carbonate. The calcium carbonate may be precipitated calcium carbonate. The compositions may be sealant compositions, rubber compositions, or adhesive compositions. The compositions according to this disclosure may have a remarkable improvement in mechanical properties compared to compositions having the same polymer matrix and a filler containing fatty acid-treated calcium carbonate. The magnitude of the improvement in mechanical properties was remarkable and unexpected, given the knowledge regarding the expected interaction between silane-treated PCC and the polymer matrix, and the interaction between fatty acid-treated PCC and the polymer matrix. For example, sealant strength was observed to increase by 122% for silicone-based polymer matrices and 76% for modified silicone-based polymer matrices compared to sealant compositions having the same base composition but containing PCC treated with fatty acids as a filler.

[0007] PCC itself exhibits poor coupling interactions with polymer rubbers, adhesives, and sealants. This is a consequence of the polar, inorganic nature of calcium carbonate and the non-polar nature of most polymer matrices. While not bound by theory, it is believed that by silane treatment of PCC, the silane acts as a coupling agent between the filler and the polymer matrix, forming a durable bond between the two materials. It was anticipated that incorporating a silane-coated substrate into a polymer matrix could improve dispersion, hydrophobicity, and polymer crosslinking, providing some improvement in mechanical properties compared to compositions without fillers; however, the degree of improvement observed in the compositions of this disclosure was greater than anticipated. Furthermore, based on conventional knowledge of the properties of fillers in polymer matrices, it was not anticipated that the use of silane-treated calcium carbonate would show such a significant improvement in mechanical properties compared to fatty acid-treated calcium carbonate.

[0008] The sealant compositions according to this disclosure may include a polymer matrix and a filler containing silane-treated calcium carbonate. The polymer matrix of the sealant composition may be any known polymer matrix used in sealant compositions. For example, the matrix may be oil-based or resin-based. Examples of polymer matrices for sealant compositions according to this disclosure include, but are not limited to, silicones, such as hydroxyl-terminated silicones and vinyl-terminated silicones, modified silicone polymers (i.e., polyether-backed polymers), butyl rubber, polyurethane, polysulfide, epichlorohydrin, fluorocarbon, isoprene, neoprene, nitrile, polysulfide, epoxy, polyvinyl acetate (PVA), PVC plastisol, hydrocarbon rubber sealants, acrylics, chlorosulfonated polyethylene, synthetic rubber hot-melt sealants, fluorosilicones and fluoropolymer sealants, styrene-butadiene copolymers, and chloroprene. For example, a sealant composition may include butyl rubber as the polymer matrix.

[0009] The adhesive compositions according to this disclosure may include a polymer matrix and a filler containing silane-treated calcium carbonate. The polymer matrix of the adhesive composition may be any known polymer matrix used in adhesive compositions. Examples of polymer matrices for adhesive compositions according to this disclosure may include, but are not limited to, silicone, epoxy, polyurethane, and mastic. Examples of mastic include asphalt or bitumen mastic. The adhesive composition may be a curing adhesive or an adhesive applied to a backing material when forming a tape. For example, the adhesive composition can be used when forming a foam-type tape to which the adhesive composition is applied to both opposing surfaces of a substrate. The adhesive composition may be a flexible composition or a rigid composition.

[0010] The rubber compositions according to this disclosure may include a polymer matrix and a filler containing silane-treated calcium carbonate. The polymer matrix of the rubber composition may be any known polymer matrix used in rubber compositions. For example, the rubber composition may be a tire rubber composition. For example, the polymer matrix of the rubber composition may be butyl rubber, natural rubber, styrene-butadiene rubber, butadiene rubber, vinyl / cis-polybutadiene rubber (A) containing 1,4-cis-polybutadiene (a) and 1,2-polybutadiene crystalline fibers, and / or nitrile-butadiene rubber. For example, the filler containing silane-treated calcium carbonate may be at least a partial substitute for silica, which is typically used in tire rubber compositions.

[0011] In any of the compositions of this disclosure, the filler may be dispersed in the polymer matrix, or, for example, substantially uniformly dispersed in the polymer matrix.

[0012] In any of the compositions of this disclosure, calcium carbonate may be precipitated calcium carbonate. Calcium carbonate may have an average particle size of about 10 nm to about 300 nm, for example, about 100 nm to about 300 nm. Precipitated calcium carbonate is about 10 nm 2 / g ~ approx. 125m 2 It can have an average surface area per gram.

[0013] In any of the compositions of this disclosure, the silane in the silane-treated calcium carbonate may be a trialkoxysilane, an organosilane, or an aminosilane. For example, the silane may be an oligomeric short-chain alkyl-functional silane such as Dynasylan® SIVO 408 (manufactured by EVONIK). For example, in a rubber composition, the silane may be a bifunctional sulfur-containing organosilane such as Si 69 (manufactured by EVONIK).

[0014] For example, in the rubber composition of this disclosure, the silane may be a sulfur-functionalized silane. For example, the silane may be bis(triethoxysilylpropyl)tetrasulfide, bis(triethoxysilylpropyl)disulfide, 3-thiocyanatopropyltriethoxysilane, or mercaptosilane. For example, the mercaptosilane may be Si 363® (manufactured by EVONIK). Other silanes commercially available from EVONIK that can be used in the rubber composition of the present invention include, for example, Si 69® (bis(triethoxysilylpropyl)tetrasulfide), Si 75® (bis(triethoxysilylpropyl)disulfide), Si 266® (bis(triethoxysilylpropyl)disulfide), and Si 264® (3-thiocyanatopropyltriethoxysilane). Such silanes may also be useful in sealant compositions that use butyl rubber or synthetic rubber-based hot melts as a polymer matrix, for example.

[0015] Calcium carbonate treated with sulfur-functionalized silane may be useful in various polymer matrices for rubber compositions of the present disclosure. For example, the polymer matrix may be or contain butyl rubber, natural rubber, styrene-butadiene rubber, butadiene rubber, vinyl / cis-polybutadiene rubber (A) containing 1,4-cis-polybutadiene (a) and 1,2-polybutadiene crystalline fibers, and / or nitrile-butadiene rubber.

[0016] In any of the compositions of this disclosure, calcium carbonate may be present in the composition in an amount of about 10% to about 50% based on the total weight of the polymer matrix.

[0017] The compositions of this disclosure have, advantageously, significantly improved tensile strength compared to compositions having fatty acid-treated calcium carbonate as a filler. For example, the compositions of this disclosure can have at least 70% greater tensile strength than compositions having fatty acid-treated calcium carbonate. For example, they can be compared to compositions having stearic acid-treated calcium carbonate.

[0018] The compositions of this disclosure have, advantageously, significantly improved modulus compared to compositions having fatty acid-treated calcium carbonate as a filler. For example, the compositions of this disclosure can have a modulus at least 70% greater than those of compositions having fatty acid-treated calcium carbonate. For example, they can be compared to compositions having stearic acid-treated calcium carbonate.

[0019] The reactivity between silane and calcium carbonate is low. As described in U.S. Patent No. 9,328,244, a process of treating calcium carbonate with silane can be carried out. For example, this method comprises mixing calcium carbonate with high-silica sodium silicate under conditions sufficient for the high-silica sodium silicate to coat the calcium carbonate, thereby providing a layer of active sites, and mixing the high-silica sodium silicate-coated calcium carbonate with hydrolyzed silane under conditions sufficient to allow the silane to react with the active sites of the high-silica sodium silicate, thereby forming silane-treated calcium carbonate. The calcium carbonate can be, for example, precipitated calcium carbonate.

[0020] The high-silica silicate can be present in an amount of about 1 wt% to about 25 wt%, based on the weight of the calcium carbonate.

[0021] The hydrolyzed silane can be added to the silicate-treated silane in an amount of about 1 wt% to about 15 wt%, based on the weight of the calcium carbonate. The silane can be, for example, a trialkoxysilane, an organosilane, or an aminosilane, as described above. For example, the silane can be Dynasylan® SIVO 408 (manufactured by Evonik).

[0022] This method can include hydrolyzing the silane immediately before adding the hydrolyzed silane to the sodium silicate-coated calcium carbonate. The hydrolysis of the silane can be performed by adding the silane dropwise to a mixture of water and a dispersion aid. The dispersion aid may be, for example, methanol. The amount of water is supplied such that the final molar ratio of water to silane is about 3:1. During the dropwise addition of the silane, the solution can be maintained at a pH of about 3.5 to about 4.5. After the addition, the mixture can be mixed for a time sufficient for the hydrolysis of the silane. [Examples]

[0023] Example 1: Silane treatment of PCC Precipitated calcium carbonate was treated with silane using the following procedure. DI water was added to a beaker in an amount that resulted in a final water:silane molar ratio of 3:1. The resulting solution was stirred with a stirring rod under ambient conditions. Methanol was then added to the DI water in an amount that achieved a final methanol:silane molar ratio of 3:1. The pH of the solution was maintained at pH 3.5 by adding a 5% acetic acid catalyst solution as needed. Silane was then added dropwise to achieve the desired water:silane and methanol:silane ratios. The solution was mixed at a temperature of approximately 80°C to 85°C for 1 to 2 hours depending on the silane being added, but for trimethoxysilane it was mixed for 1 hour and for triethoxysilane it was mixed for 2 hours. It was observed that excessive water addition inhibited hydrolysis, and that the water:silane ratio had a lower tolerance for excess water. Methanol acted as a solvent / dispersant, and its molar ratio with silane did not significantly affect the hydrolysis process. To account for evaporation, additional methanol may be added as needed.

[0024] Sodium silicate was used as the silane-PCC-silane coupling agent. An ultrafine PCC slurry was mixed with a high-silica sodium silicate solution at a concentration of approximately 3.5% by weight, based on the weight of the PCC. 3.5% by weight is equivalent to approximately 20 ml of PCC. 2 It was observed that a monolayer of the active site could be provided by appropriately coating a material (with an average surface area of ​​ / g).

[0025] The hydrolyzed silane was added to PCC coated with high-silica sodium silicate and covered with foil to retain moisture. The mixture was mixed for approximately 1 hour. The solid was filtered by Buchner funnel vacuum filtration. The wet solid was spread out, grooved to maximize airflow and heat transfer, and dried in an oven at 110°C for 24–48 hours.

[0026] Compositions were prepared using different silane-treated PCCs. Table 1 shows the composition and reaction parameters for silane treatment of the PCCs tested in the sealant compositions.

[0027] [Table 1]

[0028] [Table 2]

[0029] Silane-treated PCCs were tested using a water droplet test on a pack. Knowing that the silane used was hydrophobic, the degree of adhesion success was basically determined by the beading / absorption of water on the surface of the sample pack. The silane-treated PCCs were manually pressed onto the pack at 55 psi for 15 seconds. A higher contact angle of the water droplet on the pack correlated with a greater degree of silane adhesion. Figure 1 shows images of some trials tested using the water droplet test on a pack.

[0030] Samples 19, 21, and 23 yielded the most promising water beading results among those tested. A minimum coating amount of 7.5% by weight (theoretical value) of silane was determined when packed with 3.5% by weight of sodium silicate coupling agent. It was observed that reducing the ratio of sodium silicate while maintaining the amount of silane was detrimental to the process. Since no coating was obtained by directly adding unhydrolyzed silane to aqueous PCC, hydrolysis was determined to be a necessary first step. A low pH of approximately 4.5 or 3.5 was beneficial for efficient hydrolysis. Droplet addition of silane during hydrolysis was determined to be beneficial in mitigating the silane-silane reaction to siloxane and promoting the silane-water reaction.

[0031] Example 2: Synthesis and testing of sealant composition PCC was treated with Dynasylan® SIVO 408 and triethoxysilane. PCC was coated with silane in a 30 L reactor using the method described in Example 1. The sodium silicate-coated PCC slurry was sieved through a 325 mesh before being added to the reactor. A 28 L slurry containing a calculated 3209.2 g of solid was used as the base. In the same manner as in Example 1, 3.5 wt% sodium silicate and 7.5 wt% SIVO 408 were packed relative to the solid content. For hydrolysis, water and methanol were mixed in a molar ratio of 3:1 to SIVO 408, 24 drops of 5% acetic acid were added, and SIVO 408 was added dropwise. The hydrolysis reaction was allowed to proceed for 2 hours. The contents of the hydrolysis beaker were then poured into a reactor containing the sodium silicate-coated PCC slurry, and the adhesion reaction was allowed to proceed at 80°C for 1 hour.

[0032] The silane-treated PCC was filtered overnight under vacuum using a large Buchner funnel, and then placed in a 110°C oven for approximately 72 hours. The dried silane-treated PCC was then ground using a Mikro Atomizer®.

[0033] The PCC used to form the silane-treated PCC was ultrafine PCC (manufactured by Minerals Technology Inc.). After silane treatment, the surface area of ​​the silane-treated PCC was 14.2 m². 2 The concentration was / g. The primary particle size after silane treatment was 150 nm.

[0034] The control sample used UltraPFlex® (manufactured by Minerals Technology Inc.), a PCC filler surface-treated with stearic acid. The stearic acid-treated PCC had a primary particle size of 70 nm and 18.6 nm. 2 It had a surface area of ​​ / g. This is a commercially manufactured product by Specialty Minerals, Inc.

[0035] Silicone and modified silicone (MS) polymer sealants were formulated using silane-treated PCC as a filler to form compositions according to this disclosure. Control compositions for comparative testing utilized the same sealant base formulation but included UltraPFlex® (stearic acid-treated PCC) as a filler. Silicone sealants were prepared according to the method described in 1-Part RTV Silicon Sealant (5057-132, Roger Bauer), and MS polymer sealants were prepared according to the method described in Ross Double Planetary Mixer SOP for Adhesive / Sealant Modified Silicone Polymer. The base MS polymer sealant compositions were commercially available MS polymer-based sealants. Typical compositions are shown in Tables 1 and 2 below. The sealant compositions were filled with either silane-treated PCC or stearic acid-treated PCC as a filler.

[0036] [Table 3]

[0037] [Table 4]

[0038] The compositions according to the present invention and the control compositions were tested for surface area, coating level, moisture content, viscosity, yield stress, thixotropy, extrusion, peel adhesion, hardness, Young's modulus, tensile stress, tensile strain, elongation at break (length), and elongation at break (rate), respectively.

[0039] Uncured sealant was stretched and filled into a 5-inch x 5-inch x 1 / 8-inch jig and set to cure for 7 days in a controlled environment of 73°F and 50% relative humidity. On day 7, the cured sealant was cut into Type 4 dogbone pieces measuring 4.5 inches long x 1 inch wide (0.25 inches wide at the narrowest point). Mechanical properties testing was performed at 2 inches / min according to ASTM method D412 using an Instron Universal Tester model #68TM-R44 / 55 / 5869. The following results for mechanical strength are the average of 5 test pieces per sample. Surface area testing was performed using a Horiba SA-9600 series. Rheology testing was performed using an Anton Paar MCR 102. Tensile testing was performed using an Instron 68TM-R.

[0040] Table 4 provides test data for a silicone polymer sealant according to this disclosure having silane-treated PCC compared to a control composition having stearic acid-treated PCC.

[0041] Table 5 provides test data for the modified silicone polymer sealant according to this disclosure having silane-treated PCC compared to a control composition having stearic acid-treated PCC.

[0042] [Table 5]

[0043] [Table 6]

[0044] Figures 2-4 are graphs of the comparative tests, showing the ultimate tensile strength ("tensile stress at fracture"), tensile stress at 300% elongation, and tensile stress at 0.1, 10, and 100 seconds. -1 The viscosity at each point is shown.

[0045] In both the silicone sealant composition and the modified silicone sealant composition, the inclusion of silane-treated PCC increased the ultimate tensile strength (stress at break). For the silicone sealant, filling with the silane-treated product increased the strength by 122.3%. For the MS polymer sealant, filling with the silane-treated product increased the strength by 75.5%.

[0046] The increase in stress was also observed at 100% and 300% elongation. The difference between the composition of the present disclosure and the control composition was more significant at 300% elongation, with a 56.4% increase in stress for the silicone sealant and a 73.9% increase for the modified silicone polymer sealant.

[0047] Young's modulus increased with the addition of silane-treated PCC in both sealant types. There was a 70.3% increase for the silicone and a 96.3% increase for the modified silicone polymer sealant. It was observed that the filling of silane-treated PCC increases the sealant's resistance to elastic deformation.

[0048] At low shear rates (0.1 s -1 ), the sealants according to the present disclosure had increased viscosity compared to the control samples (a 15.6% increase for the silicone and a 28.7% increase for the modified silicone polymer sealant). However, at higher shear rates, the sealants according to the present disclosure had reduced viscosity. At 10 s -1 , the changes were -15.4% and -17.7% for the silicone and modified silicone polymer sealant, respectively. At 100 s -1 , the changes were -99.5% and -57.9% for the silicone and modified silicone polymer sealant, respectively. It was also observed that the sealants according to the present disclosure are shear-thinning compared to the control composition.

[0049] There was no significant difference in shear stress between the control composition and the composition according to this disclosure. All samples experienced cohesive failure during the peel adhesion test. The Shore A hardness on day 1 and day 7 was comparable between the control composition and the composition according to this disclosure.

[0050] The foregoing explanation is provided solely for the purpose of clarifying understanding, and modifications within the scope of this disclosure may be obvious to those skilled in the art; therefore, no unnecessary limitations should be construed therefrom.

[0051] All patents, patent applications, government publications, government regulations, and references cited herein are incorporated herein by reference in their entirety. In the event of any conflict, including definitions, this specification shall prevail.

[0052] Throughout this specification, where a compound, composition, method, and / or process is described as comprising components, steps, or materials, such compound, composition, method, and / or process is intended to comprise, essentially consist of, or consist of any combination of the listed components or materials, unless otherwise specified. Component concentrations may be expressed in weight unless otherwise specified. Combinations of components are intended to comprise homogeneous and / or heterogeneous mixtures, as can be understood by those skilled in the art in light of the foregoing disclosures.

Claims

1. polymer matrix and A filler containing silane-treated calcium carbonate, Includes, A sealant composition having improved mechanical properties compared to the sealant.

2. The sealant composition according to claim 1, wherein the polymer matrix comprises a silicone or a modified silicone polymer.

3. The sealant according to claim 1 or 2, wherein the silane is a trialkoxysilane, an organosilane, or an aminosilane.

4. The sealant composition according to any one of claims 1 to 3, wherein the calcium carbonate is precipitated calcium carbonate.

5. The sealant according to any one of claims 1 to 4, wherein the silane-treated calcium carbonate is present in an amount of about 10% to about 50% based on the total weight of the polymer matrix.

6. The sealant according to any one of claims 1 to 5, wherein the calcium carbonate has an average particle size of about 10 nm to about 300 nm.

7. The aforementioned calcium carbonate is approximately 10 m 2 / g ~ approx. 125m 2 A sealant according to any one of claims 1 to 6, having an average surface area of ​​ / g.

8. The sealant according to any one of claims 1 to 7, wherein the composition has a tensile strength at least 70% greater than that of a composition comprising the polymer matrix and a filler containing calcium carbonate surface-treated with fatty acids.

9. The sealant according to any one of claims 1 to 8, wherein the composition has an elastic modulus at least 70% greater than that of a composition comprising the polymer matrix and a filler containing calcium carbonate surface-treated with fatty acids.

10. The sealant according to claim 8 or 9, wherein the fatty acid is stearic acid.

11. XXX.

12. Adhesive matrix and A filler containing silane-treated calcium carbonate, An adhesive composition containing the following:

13. The adhesive composition according to claim 11, wherein the adhesive matrix comprises silicone, epoxy, polyurethane, and mastic, optionally asphalt mastic and bitumen mastic.

14. The adhesive composition according to claim 11 or 12, wherein the calcium carbonate is precipitated calcium carbonate.

15. The adhesive composition according to any one of claims 11 to 13, wherein the silane is trialkoxysilane, organosilane, or aminosilane.

16. The adhesive composition according to any one of claims 11 to 14, wherein the silane-treated calcium carbonate is present in an amount of about 10% to about 50% based on the total weight of the polymer matrix.

17. The adhesive composition according to any one of claims 11 to 15, wherein the calcium carbonate has an average particle size of about 10 nm to about 300 nm.

18. The aforementioned calcium carbonate is approximately 10 m 2 / g ~ approx. 125m 2 The adhesive composition according to any one of claims 11 to 16, having an average surface area per g.

19. The adhesive composition according to any one of claims 11 to 17, wherein the composition has a tensile strength at least 70% greater than that of a composition comprising the polymer matrix and a filler containing calcium carbonate surface-treated with fatty acids.

20. The adhesive composition according to any one of claims 11 to 18, wherein the composition has an elastic modulus at least 70% greater than that of a composition comprising the polymer matrix and a filler containing calcium carbonate surface-treated with fatty acids.

21. The adhesive composition according to claim 18 or 19, wherein the fatty acid is stearic acid.

22. rubber polymer matrix and A filler containing silane-treated calcium carbonate, A rubber composition containing the following:

23. The rubber composition according to claim 21, wherein the rubber polymer matrix is ​​vinyl / cis-polybutadiene rubber (A) containing tire rubber, butyl rubber, natural rubber, styrene-butadiene rubber, butadiene rubber, 1,4-cis-polybutadiene (a) and 1,2-polybutadiene crystalline fibers, and / or nitrile butadiene rubber.

24. The rubber composition according to claim 21 or 22, wherein the calcium carbonate is precipitated calcium carbonate.

25. The rubber composition according to any one of claims 21 to 23, wherein the silane is a trialkoxysilane, an organosilane, or an aminosilane.

26. The rubber composition according to claim 24, wherein the silane is a sulfur-functionalized silane.

27. The rubber composition according to claim 25, wherein the sulfur-functionalized silane is bis(triethoxysilylpropyl)tetrasulfide, bis(triethoxysilylpropyl)disulfide, 3-thiocyanatopropyltriethoxysilane, or mercaptosilane.

28. The rubber composition according to any one of claims 21 to 26, wherein the silane-treated calcium carbonate is present in an amount of about 10% to about 50% based on the total weight of the polymer matrix.

29. The rubber composition according to any one of claims 21 to 27, wherein the calcium carbonate has an average particle size of about 10 nm to about 300 nm.

30. The aforementioned calcium carbonate is approximately 10 m 2 / g ~ approx. 125m 2 The rubber composition according to any one of claims 21 to 28, having an average surface area per g.

31. The rubber composition according to any one of claims 21 to 29, wherein the composition has a tensile strength at least 70% greater than that of a composition comprising the polymer matrix and a filler containing calcium carbonate surface-treated with fatty acids.

32. The rubber composition according to any one of claims 21 to 30, wherein the composition has an elastic modulus at least 70% greater than that of a composition comprising the polymer matrix and a filler containing calcium carbonate surface-treated with fatty acids.

33. The rubber composition according to claim 30 or 32, wherein the fatty acid is stearic acid.

34. A method for producing silane-treated calcium carbonate, The method involves mixing calcium carbonate with high-silica sodium silicate under conditions sufficient for the high-silica sodium silicate to coat the calcium carbonate, thereby providing a layer of the active site. A method comprising mixing the high-silica sodium silicate coated calcium carbonate with hydrolyzed silane under conditions sufficient to allow the silane to react with the active site of the high-silica sodium silicate, thereby forming the silane-treated calcium carbonate.

35. The method according to claim 33, wherein the calcium carbonate is precipitated calcium carbonate.

36. The water-soluble film according to claim 33 or claim 34, wherein the high-silica sodium silicate is present in an amount of about 1% to about 25% by weight based on the total weight of calcium carbonate.

37. The method according to any one of claims 33 to 35, wherein the hydrolyzed silane is present in an amount of about 1% to about 15% by weight, based on the weight of the calcium carbonate.

38. The method according to any one of claims 33 to 36, wherein the silane is a trialkoxysilane, an organosilane, or an aminosilane.

39. The method according to any one of claims 33 to 37, further comprising adding the silane dropwise to a mixture of water and methanol at a pH of approximately 3.5 to 4.5 to form the hydrolyzed silane, wherein the mixture comprises water:silane in a 3:1 ratio.